Study of prevalence and associated risk factors of anaplasmosis and theileriasis in cattle - Kispotta, Sandip; Islam, Md Faruk; Hoque, Md Fazlul; Rahman, Md Shajedur; Borman, Adil; Haque, Md Anowarul; Rahman, Md Rezaur (Asian Journal of Medical and Biological Research, 2017)
A detailed cross-sectional study was carried out to investigate the prevalence and associated risk factors of theileriosis and anaplasmosis in cattle of Dinajpur district over a period of six months from January to June 2014. A total of 200 samples were randomly collected from the cattle. A pretested questionnaire was implemented to collect data on different risk factors. Blood smears were prepared and examined under microscope (100 xs) with Giemsas stain. The study revealed proportional prevalence was 10% for theileriasis and 18.5% for anaplasmosis. The percentages of theileriasis and anaplasmosis 12.61% and 22.52% were higher in female than in male animal 6.74% and 13.48% respectively. In both cases, female showed higher positivity in compare with male. The univariate logistic regression analysis revealed cattle with a herd size >10 (OR=4.3), temperature (? 103ºF) (OR=3.27), presence of tick in the body surface (OR=3.09) and record of Ivermectin treatment (OR=4.47) were found significantly associated with theileriasis prevalence (p<0.05) and irregular bathing history was found significantly associated in the case of anaplasmosis prevalence (OR=0.23). However, in multivariate analysis, temperature (? 103ºF) (OR=2.89), presence of tick in the body surface (OR=2.80) and animal with a record of Ivermectin treatment (OR=4.24) showed significant association with theileriasis and herd size >10, deep brown; white colour and bathing history were significantly associated (P < 0.05) with the anaplasmosis. Good husbandry practice and adoption of hygienic measures are needed among the high risk group or individuals to minimize the spread of the disease. Asian J. Med. Biol. Res. December 2016, 2(4): 567-576